The Passive Permeability of the Red Blood Cell to Cations - LaCelle, Paul L. (The Rockefeller University Press, 1966)
The efflux of salt from human red blood cells suspended in isotonic sucrose plus low concentrations of salt, was measured under steady-state conditions. The relationship between the efflux and the log of the salt concentration can be fitted by two straight lines with a sharp inflection point, the steeper slope occurring at concentrations below 0.2 mM NaCl. The determining factor in the rate of efflux is the ionic strength rather than the specific monovalent cations or anions and the effects are completely reversible. With an increase in temperature, the effects of reduced ionic strength are more pronounced and the inflection point is shifted toward higher salt concentrations. An increase in pH leads to an increased efflux at a given ionic strength, but the size of the pH effect is small at low ionic strength. At a given pH, the data can be fitted by a simplified form of the Goldman equation suggesting that with reduction in ionic strength, the permeability remains constant until the inflection point is reached. At that ionic strength, a sharp reversible transition to a new permeability state occurs. The permeability increases with an increase in the external but not the internal pH.